Transformasi Supervisi Akademik Berbasis Coaching Mindset dalam Meningkatkan Refleksi Profesional Guru - Maria Fitri Astuti; Muh. Hanif (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Improving education quality relies heavily on teachers’ professional reflection; however, traditional Academic Supervision (AS) is often inspectorial, hindering openness and failing to trigger sustainable self-development. This study aims to describe the implementation of Academic Supervision based on a coaching mindset using the TIRTA flow and to analyze its impact on enhancing teachers’ professional reflection. This research employed a School Action Research (SAR) design across two cycles at SMP Negeri 3 Sumbang. The subjects included the Principal and ten core subject teachers identified with low reflection levels. Data were collected using self-reflection questionnaires, coaching skill observations, and interviews. The results showed a significant increase in teachers’ professional reflection scores, rising from an average of 60.1% in the Pre-Cycle to 85.5% at the end of Cycle II, surpassing the success criteria. This quantitative improvement is supported by qualitative findings indicating that teachers became more comfortable and critical in analyzing their Pedagogical Content Knowledge (PCK) and professional beliefs. It is concluded that applying a coaching mindset through the TIRTA flow successfully transforms the supervision paradigm from inspection into a partnership, effectively fostering internal motivation and building a collaborative school culture.